2009
DOI: 10.1001/archinternmed.2009.352
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Polymyalgia Rheumatica

Abstract: The scarcity of randomized trials and the high level of heterogeneity of studies on PMR therapy do not allow firm conclusions to be drawn. However, PMR remission seems to be achieved with prednisone treatment at a dose of 15 mg/d in most patients, and reductions below 10 mg/d should preferably follow a tapering rate of less than 1 mg/mo. Methotrexate seems to exert glucocorticoid-sparing properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 42 publications
3
68
0
7
Order By: Relevance
“…For example, we found one earlier SLR reporting similar conclusions regarding the value of MTX in PMR (58). In addition, two case series were recently published on the use of leflunomide (59,60) and a few case reports are available on tocilizumab (61)(62)(63).…”
Section: Discussionmentioning
confidence: 65%
“…For example, we found one earlier SLR reporting similar conclusions regarding the value of MTX in PMR (58). In addition, two case series were recently published on the use of leflunomide (59,60) and a few case reports are available on tocilizumab (61)(62)(63).…”
Section: Discussionmentioning
confidence: 65%
“…n INTRODUCTION G lucocorticoid therapy (GCs) is a frequently used treatment for rheumatic diseases, such as Rheumatoid Arthritis (RA), Polymyalgia Rheumatica (PMR), and Connective Tissue Diseases (CTDs) such as Systemic Lupus Erythematosus (SLE) (1)(2)(3). In RA the use of low-dose GCs has a welldefined effect on disease activity (4).…”
mentioning
confidence: 99%
“…GCs represent the gold standard treatment in PMR, reducing symptoms and suppressing inflammation within a few weeks. GCs act as inhibitors of the circadian release of pro-inflammatory cytokines (such as IL-6), reducing the duration of morning stiffness (2). Although a universal regimen of daily doses of GCs in PMR is not accepted, the EULAR/ACR 2015 recommendations for the management of PMR suggest an initial GCs administration dose within a range of 12.5-25 mg prednisone (PN), and then of 10 mg for 4-8 weeks before being tapered by 1 mg every 4-8 weeks (18).…”
mentioning
confidence: 99%
“…There is some evidence for this, 2 although not enough to persuade the authors of the British Society for Rheumatology Guidelines 3 to mention it. They, like the authors of a systematic review 4 published almost synchronously, suggested methotrexate instead, but as a secondary consideration only: steroids still rule.…”
Section: The Reviewmentioning
confidence: 99%